Clinical, epidemiological and laboratory characteristics of children with febrile seizures - Shankar, Poornima; Mahamud, Shajna (International Journal of Contemporary Pediatrics, 2020)
Background: Febrile seizure is the most common type of seizure disorder that occurs in children aged 6-60 months. Recurrences are common. This study was conducted to evaluate the epidemiology, clinical profile and laboratory parameters of children presenting with febrile seizure in a teaching hospital. Methods: This was a descriptive retrospective study among children presenting with febrile seizure admitted to KIMS, Bengaluru from March (2018-2019). Children between six months to five years were included in the study while patients with prior episodes of afebrile seizures, abnormal neurodevelopment and not meeting the age criteria were excluded. Patient’s demographic and clinical data were collected from the in-patient records and analysed. Results: Among 60 children with febrile seizures were enrolled in our study with highest prevalence in males (58%) and amongst 13-24 months age group (37%). Majority (20%) presented in the monsoon season (June) and in the morning hours (43%). Simple febrile seizures and complex febrile seizures were observed in 60% and 40% respectively. Majority (73%) who developed first episode of seizure were below 24 months ago with mean age of 18.71±11.50 months. 42% had recurrence and was significantly associated with first episode of febrile seizures at age ≤1 year and family history of seizures. Upper respiratory tract infections were the commonest cause of fever. Anaemia and leucocytosis were seen in 72% and 70% cases respectively. Conclusions: Febrile seizure was observed predominantly in children below two years, simple febrile seizure being the commonest. Recurrence was common and significantly associated with the first episode of febrile seizure at the age one year or below and family history. Majority had anaemia which showed that iron deficiency anaemia could be a risk factor. Leucocytosis was present in most which could be either due to underlying infection or due to the stress of seizure itself.